Student Opinion of Instruction: System Interface Redesign Document - Faculty Senate, Valdosta State University; Downey, Steve (Valdosta State University Archives and Special Collections, 2015)
Valdosta State University. Faculty Senate. Downey, Steve. Student Opinion of Instruction: System Interface Redesign Document. Draft copy. October 21, 2015.
1 electronic document. faculty-senate_20151119_report.pdf, 23 pages. 1095621 bytes.
Keywords: Faculty Senate (Valdosta State University); Electronic records; Corporation reports